Zootherapy and rural livestock farmers in semiarid Patagonia: the transfer of animal aptitudes for health - Castillo, Lucia; Ladio, Ana H. (Ethnobiology and Conservation, 2018)
This work investigates the therapeutic value of animals to rural farmers who live on the central plateau of Chubut, Argentina. Open and in-depth interviews were carried out with 35 rural farmers from Sierra Rosada, Sierra Ventana, El Escorial and Telsen. A total of 16 biological species (12 wild and 4 domestic animals) were registered as being employed in treatment (34 registered up to the present) of different ailments, empacho being one of the main therapeutic targets. Of the domestic species, the hen (Gallus gallus domesticus) is the most versatile in its usefulness, and choique (Darwin’s Rhea) (Rhea pennata) is the most versatile wild animal. Farmers use 15 different parts of the animals, fat being the substance which is used from most species. These zootreatments imply the transfer of aptitudes (the acquisition of a certain attribute of a species through ingestion or contact with specific parts of the animal), which transforms the health and lives of the people. Our results shed light on the symbolic and symbiotic relationships woven into rural life, with their implications for the conservation and management of wild fauna.